The essence of social work as part of social security - Тищенко, Олена Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
This article examines social work as a sphere of social-protection policy. Analyzes the theoretical and legal approaches to the essence of social work. Defines the principles of social work as general principles, guidelines on which to base social work.